Litho-structural controls on orogenic gold deposits within the Sandstone greenstone belt, Yilgarn Craton, Western Australia: implications for exploration targeting. Issue 4 (2nd October 2019) - Davies, Rhys S.; Groves, David I.; Standing, Jonathan G.; Trench, Allan; Dentith, Michael; Sykes, John P.
ABSTRACT: The 920 km 2 Archean Sandstone greenstone belt lies in the central-northern part of the Southern Cross Domain of the Youanmi Terrane, Western Australia. The belt, forming an arrow-head geometry, is bounded by the Youanmi and Edale shear zones on its eastern and western margins, respectively. The belt has a total gold endowment, including historic production, resources and reserves, of approximately 62 t (2.0 Moz). Most known deposits are situated within a central-southern ultramafic domain, although this is likely a function of exploration focus. The distribution of historical exploration efforts and domaining of deposit types, based on litho-structural controls on ore formation, highlight the potential for significant undiscovered deposits, hosted within arrays of shear zones parallel and adjacent to the lithosphere-scale Youanmi and Edale shear zones.